Prevalence of dyslipidemia and risk factors in Campos dos Goytacazes, in the Brazilian State of Rio de Janeiro - Souza,Luiz José de (2003)
OBJECTIVE: To determine the prevalence of dyslipidemias in adults in the city of Campos dos Goytacazes, in the Brazilian state of Rio de Janeiro, and to identify its relation to risk factors. METHODS: Cross-sectional, population-based, observational study with sampling through conglomerates and stratified according to socioeconomic levels, sex, and age, with 1,039 individuals. Risk factors, familial history, blood pressure, anthropometric measurements, glucose, triglycerides and cholesterol were determined. RESULTS: The following prevalences were observed: of dyslipidemias 24.2%; of hypercholesterolemia, 4.2%; of elevated LDL-C, 3.5%; of low HDL-C, 18.3%; and of hypertriglyceridemia, 17.1%. The following mean levels were observed: cholesterol, 187.6± 33.7 mg/dL; LDL-C, 108.7±26.8 mg/dL; HDL-C, 48.5±7.7 mg/dL; and triglycerides, 150.1±109.8 mg/dL. The following variables showed a positive correlation with dyslipidemia: increased age (P<0.001), male sex (P<0.001), low familial income (P<0.001), familial history (P<0.01), overweight/obesity (P<0.001), waist measure (P<0.001), high blood pressure (P<0.001), and diabetes mellitus (P<0.001). The following variables had no influence on dyslipidemias: ethnicity, educational level, smoking habits, and sedentary lifestyle. CONCLUSION: The frequency of lipid changes in the population studied was high, suggesting that measures for the early diagnosis should be taken, in association with implementation of programs for primary and secondary prevention of atherosclerosis.